Penggunaan Alat Peraga Katrol sebagai Metode Pemahaman Siswa terhadap Mata Pelajaran IPA di Sekolah Dasar - Sa’diyah, Siti Halimatus; Ismanti, Septie Putri; Prayogo, Muhammad Suwignyo (Lembaga Yasin AlSys, 2023)
This research was conducted to find out about the effect of the use of visual aids on the understanding of pulley material in science subjects in SDN Pecoro 3 . This research method uses an experimental design model, namely a one-shot case study. The number of samples tested was 24 students, and the value of learning outcomes was used as the variable being tested. Then it was found that learning using visual aids had a different learning outcome value than using the lecture method, and tended to increase. The results were obtained after testing the hypothesis on the results of student learning scores, which were obtained through tests after conducting learning experiments using visual aids. The choice of pulley material itself is because many students still do not understand how the pulley system works when applied in everyday life. Then to find out the role of the use of visual aids, is it able to foster students' interest in learning. As well as to find out how big the class differences are after learning using teaching aids.